A passivated contact solar cell based on spin-coating silicon oxide and its preparation method and application
By using the Al2O3/SiO2/LiF structure of spin-coated silicon oxide in solar cells and combining low-temperature ALD technology, the problems of the complex high-temperature annealing process and the limitation of doped Si layer in existing passivation contact solar cells are solved, achieving high efficiency , low-cost electronic selective contact improves the conversion efficiency and thermal stability of solar cells.
Patent Information
- Application Number
- CN202410560763.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-08
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-05-08
AI Technical Summary
The existing passivation contact solar cells have limitations in improving power conversion efficiency (PCE), especially due to the high parasitic absorption, low doping efficiency and poor thermal stability of the doped Si layer, and the complex high-temperature annealing process, which limits the Battery performance improvement and large-scale commercial production.
Using a passivation contact structure based on spin-coated silicon oxide, the electron selective contact is prepared by setting Al2O3, SiO2 and LiF layers on the substrate in turn, combining low-temperature ALD technology and vacuum evaporation coating method, simplifying the process and reducing costs.
It achieves high passivation effect and extremely low contact resistivity, improves the conversion efficiency of solar cells, simplifies the preparation process, reduces costs, and achieves efficient electronic selective contact under low temperature conditions.
Smart Images

Figure CN118398675B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a spin-coating silicon oxide passivation contact solar cell and a preparation method and application thereof, belonging to the field of new energy. Background Art
[0002] Currently, the photovoltaic (PV) market is dominated by passivated emitter and rear contact (PERC) crystalline silicon (c-Si) solar cells, in which the carrier-selective contact is formed by heavy doping. However, several factors hinder the further improvement of the power conversion efficiency (PCE) of PERC cells. These factors include high recombination losses at the metal and Si contacts, doping-induced Auger recombination, bandgap narrowing, etc. To address the above issues, passivated contact technologies have been widely studied, for example, by dielectrically insulating SiO x The tunneling oxide passivation contact (TOPCon) composed of a layer and a heavily doped polycrystalline silicon (poly-Si) layer and the silicon heterojunction technology (HJT) with a doped hydrogenated amorphous silicon (a-Si:H) layer combined with intrinsic a-Si:H. These passivation contacts (HJT or TOPCon) based on doped Si layers have achieved impressive PCEs of more than 26% on c-Si solar cells. However, the high parasitic absorption of the doped Si layer limits the further improvement of the performance of TOPCon or HJT solar cells. In addition, there are some inherent disadvantages of passivation contacts based on doped Si layers, such as the low doping efficiency of a-Si:H and the poor thermal stability of HJT (below 250°C), as well as the high temperature thermal annealing activation process of TOPCon.
[0003] These shortcomings have triggered an in-depth exploration of doping-free carrier selective materials to replace heavily doped Si thin layers. Therefore, a simpler approach that does not rely on any doping / patterning is proposed, namely the use of doping-free carrier selective contacts (DF-CSCs), sometimes called passivation contacts, which significantly reduce carrier recombination in the contact and non-contact regions. The use of DF-CSCs can achieve high open circuit voltages and therefore have high PCEs, and are often used as new electron-selective passivation contacts for single-crystal silicon solar cells. The use of such materials is expected to reduce parasitic light absorption and simplify the manufacturing process as well as reduce costs. In addition, wide bandgap materials are also conducive to achieving large asymmetry between electron and hole conductivity, as well as suitable band offsets, which are key to achieving effective carrier selective contacts. So far, many metal compounds, such as metal oxides, fluorides, nitrides, and oxynitrides have been reported to be effective electron transport layers for c-Si solar cells. They usually have a small conduction band offset (ΔE) with c-Si. c ) and a large valence band offset (ΔE v). When used in conjunction with low work function (WF) metal compounds, it can form a good ohmic contact with c-Si, allowing photogenerated electrons to be effectively collected.
[0004] So far, metal compounds with low WF or small conduction band offset from c-Si (e.g., metal oxides and metal nitrides) have been well developed as electron selective contacts (ESCs). For example, low WF metal fluorides including MgF2, CeF3, and YF3 have been successfully used as ESCs for n-type c-Si solar cells, achieving high PCEs of over 20%. x MgO x 、TaO x 、ZnO x , TiN and TaN x ) is the most commonly studied ESC.
[0005] The output performance, especially the conversion efficiency, of the devices prepared by the above methods is still unsatisfactory. At the same time, a higher annealing temperature or a longer annealing time and number of annealing times are required, which increases the complexity of the battery preparation process and greatly limits the large-scale commercial production of such batteries. Summary of the invention
[0006] Purpose of the invention: The first purpose of the present invention is to provide a passivated contact solar cell based on spin-coating silicon oxide. The second purpose of the present invention is to provide a preparation method of the passivated contact solar cell based on spin-coating silicon oxide. The third purpose of the present invention is to provide the application of the passivated contact solar cell based on spin-coating silicon oxide in IBC or TOPCon solar cells.
[0007] Technical solution: The invention discloses a spin-coated silicon oxide passivation contact solar cell, comprising a substrate, the front surface of which is provided with p + Emitter, first Al2O3 passivation layer, SiN x Anti-reflection layer, Ag grid The back side of the substrate is provided with a second Al2O3 passivation layer, a SiO2 layer, a LiF layer and an Al electrode in sequence.
[0008] Furthermore, the front side is the side of the passivated contact solar cell facing the sun when in use, and the side facing away from the sun is the back side.
[0009] Furthermore, the substrate is made of a Cz silicon wafer with a length of 2-3 cm, a width of 2-3 cm, a thickness of 170±10 μm, and a resistivity of 1-3 Ωcm.
[0010] Furthermore, the p + The thickness of the emitter is 6-7nm.
[0011] Furthermore, the thickness of the first Al2O3 passivation layer is 7-8 nm.
[0012] Furthermore, the SiN x The thickness of the anti-reflective layer is 68-70nm.
[0013] Furthermore, the thickness of the second Al2O3 passivation layer is 0.21-0.28 nm, preferably 0.21 nm.
[0014] Furthermore, the thickness of the SiO2 layer is 18-20nm.
[0015] Furthermore, the thickness of the LiF layer is 1-1.6 nm, preferably 1.2 nm.
[0016] Furthermore, the thickness of the Al electrode is 150-200 nm.
[0017] The area of the above partition is consistent with the area of the back of the substrate, and the length and width are both 2-3 cm.
[0018] The method for preparing a passivated contact solar cell based on silicon oxide by spin coating of the present invention comprises the following steps:
[0019] (1) The substrate adopts an N-type
[100] surface, and the front side of the substrate is textured to obtain an upper surface similar to a "pyramid" shape, and the substrate is cleaned by the RCA standard process;
[0020] (2) Using the boron diffusion process to prepare p on the front side of the substrate + emitter;
[0021] (3) ALD (atomic layer deposition) + A first Al2O3 passivation layer is prepared on the front side of the emitter;
[0022] (4) SiN is deposited on the front of the first Al2O3 passivation layer by PECVD (plasma enhanced chemical vapor deposition) x Anti-reflection layer;
[0023] (5) Using silver paste on SiN by screen printing x An Ag grid is prepared on the front side of the anti-reflection layer;
[0024] (6) preparing a second Al2O3 passivation layer on the back side of the substrate by ALD method;
[0025] (7) Spin coating the SiO2 sol-gel solution on the back of the second Al2O3 passivation layer and heating and annealing;
[0026] (8) A LiF layer and an Al electrode are sequentially prepared on the back side of the second Al2O3 passivation layer spin-coated with a sol-gel solution by vacuum evaporation coating.
[0027] Furthermore, in step (2), the boron diffusion process comprises the following steps:
[0028] (1) At a temperature of 800-1100°C, oxygen is introduced to oxidize the substrate; this step helps to improve the surface properties of the substrate and provides a good foundation for subsequent boron diffusion;
[0029] (2) Maintain the temperature after oxidation or raise the temperature to 900-1100°C, introduce a boron source, oxygen and nitrogen for boron diffusion. The boron source is boron trichloride (BCl3). The high temperature releases the boron element from the boron source, and then deposits on the substrate surface and gradually diffuses into the interior to form a PN junction.
[0030] (3) After the boron diffusion is completed, the introduction of the boron source, oxygen and nitrogen is stopped, and the temperature is gradually lowered to cool the substrate, fix the position of the boron element in the substrate, and form a stable PN junction.
[0031] Furthermore, by repeating step (6), a second Al2O3 passivation layer of different thicknesses can be obtained, preferably with a thickness of 3 cycles to 4 cycles, and most preferably 3 cycles.
[0032] Furthermore, in step (7), when spin coating the SiO2 sol-gel solution, the volume of the SiO2 sol-gel solution is 20-40 μL, preferably 30 μL, the rotation speed is 3500-4500 rpm / min, preferably 4000 rpm / min, and the spin coating time is 30-40 s, preferably 30 s.
[0033] Furthermore, in step (7), the temperature of the heating annealing treatment is 100-110° C., and the time of the heating annealing treatment at 100° C. is preferably 2-4 min, preferably 3 min.
[0034] Furthermore, in step (8), the temperature of the vacuum evaporation coating is 1180-2470°C and the vacuum degree is 7x10 -4 Pa below, the speed of evaporation is The speed of evaporating Al electrode is In this process, the evaporation temperature of LiF is 1180°C, and the evaporation temperature of the Al electrode layer is about 2470°C. This means that when performing thermal evaporation deposition of LiF and Al, the temperature of the heating source needs to be adjusted to this range to ensure that LiF and Al can effectively transform from solid to gaseous state and then deposit on the surface of the target object to form a thin film. During the entire evaporation process, a certain vacuum degree needs to be maintained to reduce the influence of gas molecules on the evaporation process. The vacuum condition of the thermal evaporation deposition of the present invention needs to reach 7x10 -4 Pa or less. The evaporation speed is an important factor affecting the quality of the film. Too fast an evaporation speed may cause uneven film or defects, while too slow an evaporation speed may prolong the production time. Therefore, in practical applications, the evaporation speed needs to be adjusted according to specific equipment and technical requirements to obtain the best evaporation effect. The rate of evaporation of the LiF layer in the present invention is The rate of evaporation of Al electrode is
[0035] Furthermore, the front side mentioned above is the side of the passivated contact solar cell facing the sun when in use, and the side facing away from the sun is the back side.
[0036] The invention discloses an application of a spin-coating silicon oxide passivation contact solar cell in the preparation of an IBC solar cell or a TOPCon solar cell.
[0037] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0038] (1) The present invention provides an effective electron selective contact solar cell through simple spin coating and low-temperature ALD technology, and prepares the electron selective contact structure of Al2O3 / SiO2 / LiF. From the characterization of this structure, there are two reasons why the device achieves such excellent results: ① The LiF layer and the Al layer diffuse into the SiO2 film during the preparation process, which slightly reduces the contact resistivity on the back side. ② More importantly, the SiO2 film prepared by spin coating has a large number of nano-scale cracks, and the LiF layer and the Al layer form a transmission structure similar to a hole through these cracks, which determines that the back structure obtains an extremely low contact resistivity. Therefore, the Al2O3 / SiO2 / LiF obtained by the method of this patent achieves a high passivation effect while also obtaining an extremely low contact resistivity, and finally achieves a high conversion efficiency.
[0039] (2) The method of the present invention is simple to prepare, has low preparation cost and low time cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 A schematic diagram of the structure of a passivated contact solar cell provided by the present invention;
[0041] Figure 2 A high-angle annular dark-field scanning transmission electron microscope of the back side of an N-type solar cell prepared in Example 1;
[0042] (HAADF-STEM) images, EDX element scans and element line scans;
[0043] Figure 3 JV curves of solar cells prepared with Al2O3 / SiO2 / LiF electron selective contact in Example 1, Al2O3 / LiF electron selective contact in Comparative Example 1, Al2O3 / SiO2 electron selective contact in Comparative Example 2, and Al2O3 electron selective contact in Comparative Example 3;
[0044] Figure 4 EQE curves of solar cells prepared with Al2O3 / SiO2 / LiF electron selective contact in Example 1, Al2O3 / LiF electron selective contact in Comparative Example 1, Al2O3 / SiO2 electron selective contact in Comparative Example 2, and Al2O3 electron selective contact in Example 3; DETAILED DESCRIPTION
[0045] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0046] Example 1
[0047] like Figure 1 As shown, the passivation contact solar cell based on spin coating silicon oxide provided by the present invention comprises a substrate 1, and the front side of the substrate 1 is provided with p + Emitter 5, first Al2O3 passivation layer 4, SiN x The anti-reflection layer 3 and the Ag grid 2, the back side of the substrate 1 is provided with a second Al2O3 passivation layer 9, a SiO2 layer 6, a LiF layer 7 and an Al electrode 8 in sequence.
[0048] The front side referred to above is the side of the passivated contact solar cell facing the sun when in use, and the back side is the side facing away from the sun.
[0049] The substrate 1 uses an N-type
[100] face Cz silicon wafer with a length of 2-3 cm, a width of 2-3 cm, a thickness of 170±10 μm, and a resistivity of 1-3 Ωcm.
[0050] p + The thickness of the emitter 5 is 6-7nm, the thickness of the first Al2O3 passivation layer 4 is 7-8nm, and the thickness of the SiN x The thickness of the anti-reflection layer 3 is 68-70 nm.
[0051] The thickness of the second Al2O3 passivation layer 9 is 0.21-0.28 nm (ie, 3 cycles-4 cycles), the thickness of the SiO2 layer 6 is 18-20 nm, the thickness of the LiF layer 7 is 1-1.2 nm, and the thickness of the Al electrode 8 is 150-200 nm.
[0052] In the above scheme, after the substrate 1 is textured, an upper surface similar to a "pyramid" shape is obtained on the front side thereof.
[0053] S N x The anti-reflection layer 3 is deposited by PECVD (plasma enhanced chemical vapor deposition) method. x A large number of fixed positive charges and free hydrogen atoms are formed in the anti-reflection layer 3. These fixed positive charges form a built-in electric field at the surface of the battery, which puts the surface in an inversion state, thereby reducing the probability of carriers meeting and recombination on the surface and reducing the surface recombination velocity. This passivation effect helps to improve the photoelectric conversion efficiency of solar cells.
[0054] On the other hand, the first Al2O3 passivation layer 4 is prepared by ALD (atomic layer deposition). The first Al2O3 passivation layer 4 has a high fixed negative charge density and a strong field effect passivation effect. This means that the first Al2O3 passivation layer 4 can effectively reduce the non-radiative recombination on the battery surface and further improve the efficiency of the battery. x The application of the anti-reflection layer 3 and the first Al2O3 passivation layer 4 not only enhances the passivation effect, but also improves the overall performance of the battery by improving the charge distribution on the battery surface and reducing surface recombination.
[0055] p + The emitter 5 is prepared by a boron diffusion process, that is, oxygen is introduced at a temperature of 800-1100°C to oxidize the substrate 1; this step helps to improve the surface properties of the substrate and provides a good foundation for subsequent boron diffusion; then the temperature after oxidation is maintained or raised to 900-1100°C, and a boron source, oxygen and nitrogen are introduced for boron diffusion, the boron source is boron trichloride, and the boron element is released from the boron source by high temperature, and then deposited on the surface of the substrate 1 and gradually diffused inward to form a PN junction; after the boron diffusion is completed, the boron source, oxygen and nitrogen are stopped, and the temperature is gradually lowered to cool the substrate 1, fix the position of the boron element in the substrate 1, and form a stable PN junction.
[0056] The second Al2O3 passivation layer 9 on the back of the solar cell is still prepared by the ALD method, and then the SiO2 layer 6 is prepared by the spin coating method to improve the passivation effect of the device. Finally, the LiF layer 7 is prepared by thermal evaporation, and an Al electrode 8 is superimposed on the outside of the LiF layer 7 to form a LiF / Al stack with a low work function, and the LiF layer 7 side of the LiF / Al stack is covered on the SiO2 layer 6. The low work function will induce band bending near the substrate 1, which is helpful to transport electrons and block holes, so that the overall performance of the battery is improved.
[0057] Preparation of N-type solar cells
[0058] (1) A solar-grade Cz silicon wafer with an N-type
[100] surface having a pyramid on the front side after texturing, a length of 2 cm and a width of 2 cm was used. The thickness of the Cz silicon wafer was 170±10μm, and the resistivity was 1-3Ωcm, which was recorded as an N-type substrate.
[0059] The steps of Cz silicon wafer texturing are as follows: the solution for cleaning the silicon wafer is a 15% by mass NaOH aqueous solution. The cleaning solution can be used to remove organic impurities on the surface of the silicon wafer, such as dirt and fingerprints, as well as impurity ions and mechanical damage layers on the surface of the silicon wafer, so that the subsequent texturing chemical reaction is more complete and uniform. The temperature of the cleaning solution in the tank is set at 80°C and the cleaning time is 1 minute.
[0060] Next is the texturing process. 2.5% NaOH and 10% isopropyl alcohol (IPA) etching solutions are added to the texturing tank respectively. The temperature is 80°C and the reaction time is 15 minutes. 3% Na2SiO3 is added to the solution before the reaction. The texturing effect is better and the reflectivity is reduced, reaching a minimum of 9.5%. During the texturing process, the solution needs to be stirred constantly so that the etching solution can flow continuously and the corrosion rate remains fast, which is conducive to the formation of an ideal suede in a short time.
[0061] Finally, the silicon wafer after texturing is cleaned and blown dry.
[0062] (2) A sol-gel solution with a concentration of 0.06 mol / L of tetraethyl orthosilicate (TEOS) was synthesized by dissolving a tetraethyl orthosilicate (TEOS) precursor in isopropanol and then ultrasonically treating the solution for 30 min. Subsequently, deionized (DI) water with a molar ratio of H2O:TEOS of 2.22 and a nitric acid solution with a concentration of 0.039 mol / L were gradually added. The solution was then placed outdoors for aging for 10 h.
[0063] (3) Clean the original silicon wafer using the RCA standard process.
[0064] (4) Boron diffusion process is used to prepare a 6nm thick P + The emitter stage 5 is then ALD-treated in p+ A first Al2O3 passivation layer 4 with a thickness of 7 nm is deposited on the emitter 5, and a SiN layer with a thickness of 70 nm is deposited on the first Al2O3 passivation layer 4 using the PECVD technique. x Anti-reflection layer 3. The temperature during boron diffusion is 1000° C., and the flow rates of boron trichloride, oxygen and nitrogen are 500 sccm, 1000 sccm and 2000 sccm respectively.
[0065] (5) Finally, silver paste is used on SiN by screen printing. x An Ag grid is prepared on the front side of the anti-reflection layer 3 . The thickness of the Ag grid is 250 nm, and the distance between two adjacent Ag grids is 0.2 mm.
[0066] (6) On the back side of the N-type substrate, the N-type substrate processed in step (5) is placed in an ALD chamber, the chamber is kept in a vacuum state and at a constant temperature of 150°C, the quick valve of the trimethylaluminum source bottle is opened, and trimethylaluminum is introduced into the ALD chamber. The trimethylaluminum source bottle is kept at a constant temperature of 30°C, the quick valve is opened for 25ms and then closed, and nitrogen is purged for 25-40s; then the quick valve of the DI water is opened, the DI water source bottle is kept at a constant temperature of 35°C, the quick valve is opened for 7-12ms and then closed, and nitrogen is purged for 25-40s. At this time, an Al2O3 film, i.e., a second Al2O3 passivation layer 9, will grow on the back side of the N-type substrate.
[0067] By repeating step (6), Al2O3 films of different thicknesses can be prepared. In this example, step (6) is repeated for 2 cycles, i.e., the thickness is 3 cycles. The final Al2O3 film thickness is obtained by testing the contact resistivity of Al2O3 films of different thicknesses.
[0068] (7) Spin-coat 30 μl of the SiO2 sol-gel solution aged in step (2) on the outside of the second Al2O3 passivation layer 9, and place the Al2O3-plated device on a spin coater tray at a rotation speed of 4000 rpm / min for 30 seconds to produce a SiO2 layer 6 with a thickness of about 20 nm.
[0069] (8) Place the spin-coated N-type substrate on a heating table at 100°C and anneal for 3 minutes.
[0070] (9) A 1.2 nm thick LiF layer 7 was prepared by vacuum evaporation coating, and a 200 nm thick Al electrode 8 was further evaporated on the layer 7 to obtain a LiF / Al stack, and a c-Si / Al2O3 / SiO2 / LiF / Al contact structure N-type solar cell was obtained. The temperature during vacuum evaporation coating was 1180-2470°C, and the vacuum degree was 7x10 -4 Pa or less, the rate of evaporation of LiF layer (7) is The speed of evaporating Al electrode (8) is
[0071] The back cross section of the N-type solar cell was analyzed by STEM and EDX line scan. The results are as follows: Figure 2 shown. Figure 2 The high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) image, EDX element scanning map and element line scanning map of the back side of the N-type solar cell prepared in Example 1; wherein, (a) is the HAADF-STEM image of the cross-section of the back side of the N-type solar cell prepared in Example 1; (b) is the HAADF-STEM image of the c-Si / Al2O3 / SiO2 / LiF / Al interface on the back side of the N-type solar cell prepared in Example 1; (c) is the EDX element scanning map of the back side of the N-type solar cell prepared in Example 1; (d) is the EDX line scanning map of the c-Si / Al2O3 / SiO2 / LiF / Al interface on the back side of the N-type solar cell prepared in Example 1.
[0072] Depend on Figure 2 In (b), it can be seen that the back of the N-type solar cell is composed of 200nm Al, 1.2nm LiF, 20nm SiO2 and 0.21nm Al2O3. Figure 2 In (c) and (d), it can be found that the F element and Al diffuse into the SiO2 layer, and the diffusion of the low work function film helps the transmission of electrons.
[0073] in, Figure 3 and 4 The JV curves and EQE curves of Example 1 and Comparative Examples 1-3 are shown.
[0074] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.48 mA·cm -2 The short-circuit current density (J sc ), 674.48mV open circuit voltage (V oc ) and a fill factor (FF) of 82.25%, and finally an efficiency of 22.46% was obtained, as shown in Table 1.
[0075] Example 2
[0076] The difference between the experimental process and Example 1 is that the thickness of the second Al2O3 passivation layer 9 prepared by the ALD method is different, that is, the thickness is 1 cycle.
[0077] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.12 mA·cm -2 J sc, 648.31mV V oc and 81.55% FF, and finally an efficiency of 21.22% was obtained.
[0078] Example 3
[0079] The difference between the experimental process and Example 1 is that the thickness of the second Al2O3 passivation layer 9 prepared by the ALD method is different, that is, the thickness is 2 cycles.
[0080] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.25 mA·cm -2 J sc , 652.2mV V oc and 80.94% FF, and finally an efficiency of 21.25% was obtained.
[0081] Example 4
[0082] The difference between the experimental process and Example 1 is that the thickness of the second Al2O3 passivation layer 9 prepared by the ALD method is different, that is, the thickness is 4 cycles.
[0083] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40 mA·cm -2 J sc , 674.16mV V oc and 74.25% FF, and finally an efficiency of 20.31% was obtained.
[0084] Example 5
[0085] The difference between the experimental process and Example 1 is that the thickness of the second Al2O3 passivation layer 9 prepared by the ALD method is different, that is, the thickness is 5 cycles.
[0086] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.12 mA·cm -2 J sc , 679.63mV V oc and 73.89% FF, and finally an efficiency of 19.51% was obtained.
[0087] Example 6
[0088] The difference between the experimental process and Example 1 is that the thickness of the second Al2O3 passivation layer 9 prepared by the ALD method is different, that is, the thickness is 8 cycles.
[0089] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.43 mA·cm -2 J sc , 663.92mV V oc and 32.46% FF, and finally an efficiency of 8.71% was obtained.
[0090] In summary, the solar cell parameters are better when the thickness of the second Al2O3 passivation layer 9 is within the range of 1-4 cycles (0.21-0.28nm), and the parameters are the best when the thickness is 3 cycles, with the highest efficiency reaching 22.46%. When the thickness exceeds 4 cycles, that is, starting from the 5th cycle, the solar cell parameters drop significantly, among which the most obvious drop is FF. This shows that the conductivity of Al2O3 drops significantly after more than 4 cycles.
[0091] Example 7
[0092] The difference between the experimental process and Example 1 is that the thickness of the LiF layer 7 prepared by the ALD method is different, that is, the thickness is 1 nm.
[0093] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 39.65 mA·cm -2 J sc , 674.35mV V oc and 79.43% FF, and finally an efficiency of 21.24% was obtained.
[0094] Example 8
[0095] The difference between the experimental process and Example 1 is that the thickness of the LiF layer 7 prepared by ALD is different, that is, the thickness is 1.4 nm.
[0096] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.79 mA·cm -2 J sc , 671.41mV V oc and 79.73% FF, and finally an efficiency of 21.84% was obtained.
[0097] Example 9
[0098] The difference between the experimental process and Example 1 is that the thickness of the LiF layer 7 prepared by ALD is different, that is, the thickness is 1.6 nm.
[0099] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.73 mA·cm -2 J sc , 661.83mV V oc and 81.86% FF, and finally an efficiency of 22.07% was obtained.
[0100] Example 10
[0101] The difference between the experimental process and Example 1 is that the thickness of the LiF layer 7 prepared by ALD is different, that is, the thickness is 2.5 nm.
[0102] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.57 mA·cm -2 J sc , 668.08mV V oc and 63.74% FF, and finally an efficiency of 17.21% was obtained.
[0103] Embodiment 11
[0104] The difference between the experimental process and Example 1 is that the thickness of the LiF layer 7 prepared by ALD is different, that is, 3 nm.
[0105] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a power of 39.88 mA·cm -2 J sc , 662.48mV V oc and 46.73% FF, and finally an efficiency of 12.34% was obtained.
[0106] In summary, the parameters of solar cells with LiF thickness in the range of 1-1.6nm are better, and the parameters are the best when the thickness is 1.2nm, with the highest efficiency reaching 22.46%. When the thickness reaches 2.5nm, the parameters of solar cells drop significantly, and the most obvious drop is FF. This shows that when the thickness of LiF reaches 2.5nm, the conductivity drops significantly.
[0107] Example 12
[0108] The difference between the experimental process and Example 1 is that after the SiO2 film is spin-coated, the annealing time is 1 min at 100°C.
[0109] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.35 mA·cm -2 J sc , 667.64mV V oc and 76.55% FF, and finally an efficiency of 20.62% was obtained.
[0110] Embodiment 13
[0111] The difference between the experimental process and Example 1 is that after the SiO2 film is spin-coated, the annealing time is 2 minutes at 100°C.
[0112] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.74 mA·cm -2 J sc , 670.16mV V oc and 80.72% FF, and finally an efficiency of 22.04% was obtained.
[0113] Embodiment 14
[0114] The difference between the experimental process and Example 1 is that after the SiO2 film is spin-coated, the annealing time is 4 minutes at 100°C.
[0115] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.4 mA·cm -2 J sc , 661.95mV V oc and 82.16% FF, and finally an efficiency of 21.97% was obtained.
[0116] Embodiment 15
[0117] The difference between the experimental process and Example 1 is that after the SiO2 film is spin-coated, the annealing time is 5 minutes at 100°C.
[0118] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.09 mA·cm -2 J sc , 659.16mV V oc and 77.34% FF, and finally an efficiency of 20.44% was obtained.
[0119] In summary, the annealing time after spin coating is kept within the range of 2-4 minutes, and the best is 3 minutes. The annealing time within 0-1 minute is not enough to cause cracks in the spin-coated SiO2, and the annealing time exceeds 5 minutes, which will damage the spin-coated SiO2 layer. Both of these situations will lead to a decrease in the conductivity of the device.
[0120] Example 16
[0121] The difference between the experimental process and Example 1 is that after the SiO2 film is spin-coated, an annealing treatment at 80°C is performed for 3 minutes.
[0122] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.03 mA·cm -2 J sc , 670mV V oc and 73.17% FF, and finally an efficiency of 19.62% was obtained.
[0123] Embodiment 17
[0124] The difference between the experimental process and Example 1 is that after the SiO2 film is spin-coated, an annealing treatment at 90°C is performed for 3 minutes.
[0125] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.1 mA·cm -2 J sc , 675.89mV V oc and 80.92% FF, and finally an efficiency of 21.93% was obtained.
[0126] Embodiment 18
[0127] The difference between the experimental process and Example 1 is that after the SiO2 film is spin-coated, an annealing treatment at 110°C is performed for 3 minutes.
[0128] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.41 mA·cm -2 J sc , 672.07mV V oc and 82.26% FF, and finally an efficiency of 21.76% was obtained.
[0129] Embodiment 19
[0130] The difference between the experimental process and Example 1 is that after the SiO2 film is spin-coated, an annealing treatment at 120°C for 3 minutes is performed.
[0131] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a power of 39.07 mA cm -2 J sc , 661.64mV V oc and 75.1% FF, and finally an efficiency of 19.26% was obtained.
[0132] In summary, the annealing time after spin coating is better when it is kept within 90-110℃, among which 100℃ is the best parameter. Annealing temperature within 0-80℃ is not enough to cause cracks in the spin-coated SiO2, and when the annealing temperature exceeds 100℃, the spin-coated SiO2 layer will be damaged. Both situations will lead to a decrease in the conductivity of the device.
[0133] Embodiment 20
[0134] The difference between the experimental process and Example 1 is that the volume of the solution used in the spin coating process is 10 μL.
[0135] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 39.25 mA·cm -2 J sc , 659.53mV V oc and 77.72% FF, and finally an efficiency of 20.28% was obtained.
[0136] Embodiment 21
[0137] The difference between the experimental process and Example 1 is that the volume of the solution used in the spin coating process is 20 μL.
[0138] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.25 mA·cm -2 J sc , 652.2mV V oc and 80.09% FF, and finally an efficiency of 21.25% was obtained.
[0139] Embodiment 22
[0140] The difference between the experimental process and Example 1 is that the volume of the solution used in the spin coating process is 40 μL.
[0141] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a power of 39.9 mA cm -2 J sc , 662.25mV V oc and 81.89% FF, and finally an efficiency of 21.64% was obtained.
[0142] Embodiment 23
[0143] The difference between the experimental process and Example 1 is that the volume of the solution used in the spin coating process is 60 μL.
[0144] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.77 mA·cm -2 J sc , 665.08mV V oc and 78.01% FF, and finally an efficiency of 20.87% was obtained.
[0145] In summary, the volume of the spin coating solution is in the range of 20-40μL to obtain better parameters, among which the volume of 30μL has the best parameters. When the volume is less than 10μL or greater than 60μL, the V oc Both FF and F will decrease significantly.
[0146] Embodiment 24
[0147] The difference between the experimental process and Example 1 is that the rotation speed of the coating machine during the spin coating process is set to 3000 rpm / min.
[0148] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 39.41 mA·cm -2 J sc , 662.29mV V oc and 78.31% FF, and finally an efficiency of 20.44% was obtained.
[0149] Embodiment 25
[0150] The difference between the experimental process and Example 1 is that the rotation speed of the coating machine during the spin coating process is set to 3500 rpm / min.
[0151] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.34 mA·cm -2 J sc, 661.85mV V oc and 80.67% FF, and finally an efficiency of 21.54% was obtained.
[0152] Embodiment 26
[0153] The difference between the experimental process and Example 1 is that the rotation speed of the coating machine during the spin coating process is set to 4500 rpm / min.
[0154] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a current of 40.12 mA·cm -2 J sc , 648.31mV V oc and 81.55% FF, and finally an efficiency of 21.22% was obtained.
[0155] Embodiment 27
[0156] The difference between the experimental process and Example 1 is that the rotation speed of the coating machine during the spin coating process is set to 5000 rpm / min.
[0157] The c-Si / Al2O3 / SiO2 / LiF / Al electron selective contact solar cell prepared in this example was tested and obtained a power of 39.7 mA cm -2 J sc , 664.94mV V oc and 74.3% FF, and finally an efficiency of 19.61% was obtained.
[0158] In summary, better parameters can be obtained when the spin coating speed is in the range of 3500-4500rpm / min, and the best parameters are obtained when the speed is 4000rpm / min. When the speed is lower than 3000rpm / min or higher than 5000rpm / min, the FF of the device will drop significantly.
[0159] By comparing Examples 1-27, it can be seen that the optimal thickness of the second Al2O3 passivation layer 9 is 3 ALD cycles (0.21nm), the optimal thickness of the LiF layer 7 is 1.2nm, the optimal annealing time after spin coating is 3min, the optimal annealing temperature is 100°C, the optimal rotation time during spin coating is 30s, the solution volume is 30μL, and the optimal rotation speed during spin coating is 4000rpm / min, which is the optimal champion efficiency of Example 1 of the present application.
[0160] Comparative Example 1
[0161] The experimental process is different from that of Example 1 in that no SiO2 sol-gel solution is prepared, and no spin coating is performed on the back of the solar cell, that is, steps (2), (7) and (8) are removed. Finally, a c-Si / Al2O3 / LiF / Al electron selective contact solar cell is prepared.
[0162] Figure 3 and 4 The JV curve and EQE curve of Comparative Example 1 are shown.
[0163] The c-Si / Al2O3 / LiF / Al electron selective contact solar cell prepared in this comparative example was tested and obtained a current of 37.61 mA·cm -2 J sc , 603.05mV V oc and 81.41% FF, and finally an efficiency of 18.46% was obtained, as shown in Table 1.
[0164] Comparative Example 2
[0165] The difference between the experimental process and Example 1 is that the LiF film is not prepared by thermal evaporation, that is, the preparation of the 1.2 nm LiF layer 7 in step (8) is removed. Finally, a c-Si / Al2O3 / SiO2 / Al electron selective contact solar cell is prepared.
[0166] Figure 3 and 4 The JV curve and EQE curve of Comparative Example 2 are shown.
[0167] The c-Si / Al2O3 / SiO2 / Al electron selective contact solar cell prepared in this comparative example was tested and obtained a current of 35.69 mA cm -2 J sc , 592.61mV V oc and 80.82% FF, and finally an efficiency of 17.09% was obtained, as shown in Table 1.
[0168] Comparative Example 3
[0169] The implementation process is different from Example 1 in that a sol-gel solution is not prepared, spin coating is not performed on the back of the solar cell, that is, steps (2), (7) and (8) are removed, and LiF film is not prepared by thermal evaporation, that is, the preparation of the 1.2 nm LiF layer 7 in step (9) is removed.
[0170] Figure 3 and 4 The JV curve and EQE curve of Comparative Example 3 are shown.
[0171] Finally, the c-Si / Al2O3 / Al electron selective contact solar cell prepared in the comparative example obtained a 34.88 mA cm -2 J sc , 547.98mV V oc and 77.88% FF, and finally an efficiency of 14.88% was obtained, as shown in Table 1.
[0172] Table 1
[0173] Solar cells η[%] <![CDATA[J sc [mA cm -2 ]]> <![CDATA[V oc [mV]]]> FF[%] <![CDATA[Al2O3 / SiO2 / liF]]> 22.46 40.48 674.48 82.25 <![CDATA[Al2O3 / liF]]> 18.46 37.61 603.05 81.41 <![CDATA[Al2O3 / SiO2]]> 17.09 35.69 592.61 80.82 <![CDATA[Al2O3]]> 14.88 34.88 547.98 77.88
[0174] According to the specific parameters shown in Table 1, compared with the solar cell without spin coating of SiO2 but with the same other steps, the N-type solar cell prepared in Example 1 has all-round improvement in photovoltaic parameters after the simple spin coating method, among which 40.48 mA·cm -2 The short-circuit current density (J sc ), 674.48mV open circuit voltage (V oc ) and a fill factor (FF) of 82.25%, and finally achieved a championship efficiency of 22.46%.
[0175] Figure 3 JV curves of solar cells prepared with Al2O3 / SiO2 / LiF electron selective contact in Example 1, Al2O3 / LiF electron selective contact in Comparative Example 1, Al2O3 / SiO2 electron selective contact in Comparative Example 2, and Al2O3 electron selective contact in Comparative Example 3; Figure 4 EQE curves of solar cells prepared with Al2O3 / SiO2 / LiF electron selective contact in Example 2, Al2O3 / LiF electron selective contact in Comparative Example 1, Al2O3 / SiO2 electron selective contact in Comparative Example 2, and Al2O3 electron selective contact in Example 3.
[0176] By comparing Examples 1-27 and Comparative Examples 1-3, it can be seen that the present invention successfully manufactures a new type of solar cell using an n-type c-Si / Al2O3 / SiO2 / LiF / Al contact structure, in which the Al2O3 / SiO2 / LiF film serves as an electron selective passivation contact. An effective electron selective contact is provided by simple spin coating and low temperature ALD technology and film optimization. Compared with the comparative example 1 without spin coating SiO2 film, the solar cell with c-Si / Al2O3 / SiO2 / LiF / Al contact structure exhibits excellent surface passivation performance and conductivity. In addition, the N-type solar cell based on the c-Si / Al2O3 / SiO2 / LiF / Al contact structure is superior to the known V oc,I sc The performances of FF and the like are better than those of the solar cells obtained in Comparative Examples 1-3. Finally, the present invention successfully achieves the highest championship efficiency of 22.46% for N-type solar cells based on spin-coated SiO2 thin films, which is much higher than 18.46%, 17.09% and 14.88% of the solar cells based on Comparative Examples 1-3.
Claims
1. A passivated contact solar cell based on spin-coated silicon oxide, characterized in that: It comprises a substrate (1), the front surface of the substrate (1) is provided with p + Emitter (5), first Al2O3 passivation layer (4), SiN x An anti-reflection layer (3), an Ag grid (2), and a second Al2O3 passivation layer (9), a SiO2 layer (6), a LiF layer (7) and an Al electrode (8) are sequentially provided on the back side of the substrate (1); The method for preparing a passivated contact solar cell based on spin coating silicon oxide comprises the following steps: (1) the substrate (1) adopts an N-type [100] surface, and the front surface of the substrate (1) is textured to obtain a "pyramid" shaped upper surface, and the substrate (1) is cleaned by RCA standard process; (2) Prepare p on the front side of substrate (1) by using boron diffusion process + Emitter (5); (3) Through the ALD method + A first Al2O3 passivation layer (4) is prepared on the front side of the emitter (5); (4) SiN is deposited on the front of the first Al2O3 passivation layer (4) by PECVD x Anti-reflection layer (3); (5) Using silver paste on SiN by screen printing x A Ag grid (2) is prepared on the front side of the anti-reflection layer (3); (6) preparing a second Al2O3 passivation layer (9) on the back side of the substrate (1) by an ALD method; (7) Spin coating the SiO2 sol-gel solution on the back side of the second Al2O3 passivation layer (9), and heating and annealing; (8) A LiF layer (7) and an Al electrode (8) are sequentially prepared on the back side of the second Al2O3 passivation layer (9) spin-coated with a sol-gel solution by a thermal vacuum evaporation coating method.
2. The spin-coated silicon oxide passivated contact solar cell according to claim 1, characterized in that: The front side is the side of the passivated contact solar cell facing the sun when in use, and the side facing away from the sun is the back side.
3. The spin-coated silicon oxide passivated contact solar cell according to claim 1, characterized in that: The material of the substrate (1) is a Cz silicon wafer, which has a length of 2-3 cm, a width of 2-3 cm, a thickness of 170±10 μm, and a resistivity of 1-3Ωcm.
4. The spin-coated silicon oxide passivated contact solar cell according to claim 1, characterized in that: The p + The thickness of the emitter (5) is 6-7 nm, the thickness of the first Al2O3 passivation layer (4) is 7-8 nm, and the SiN x The thickness of the anti-reflection layer (3) is 68-70 nm, the thickness of the second Al2O3 passivation layer (9) is 0.21-0.28 nm, the thickness of the SiO2 layer (6) is 18-20 nm, the thickness of the LiF layer (7) is 1-1.6 nm, and the thickness of the Al electrode (8) is 150-200 nm.
5. The method for preparing a passivated contact solar cell based on spin coating silicon oxide according to any one of claims 1 to 4, comprising the following steps: (1) The substrate (1) adopts an N-type [100] surface, and the front side of the substrate (1) is textured to obtain a "pyramid" shaped upper surface, and the substrate (1) is cleaned by the RCA standard process; (2) Prepare p on the front side of substrate (1) by using boron diffusion process + Emitter (5); (3) Through the ALD method + A first Al2O3 passivation layer (4) is prepared on the front side of the emitter (5); (4) SiN is deposited on the front of the first Al2O3 passivation layer (4) by PECVD x Anti-reflection layer (3); (5) Using silver paste on SiN by screen printing x A Ag grid (2) is prepared on the front side of the anti-reflection layer (3); (6) preparing a second Al2O3 passivation layer (9) on the back side of the substrate (1) by an ALD method; (7) Spin coating the SiO2 sol-gel solution on the back side of the second Al2O3 passivation layer (9), and heating and annealing; (8) A LiF layer (7) and an Al electrode (8) are sequentially prepared on the back side of the second Al2O3 passivation layer (9) spin-coated with a sol-gel solution by a thermal vacuum evaporation coating method.
6. The preparation method according to claim 5, characterized in that: In step (2), the boron diffusion process comprises the following steps: (1) introducing oxygen at a temperature of 800-1100° C. to perform oxidation treatment on the substrate (1); (2) maintaining the temperature after oxidation or raising the temperature to 900-1100° C., introducing a boron source, oxygen and nitrogen to diffuse boron, wherein the boron source is boron trichloride, and the boron element is released from the boron source by high temperature, and then deposited on the surface of the substrate (1) and gradually diffused into the interior to form a PN junction; (3) After the boron diffusion is completed, the introduction of the boron source, oxygen and nitrogen is stopped, and the temperature is gradually lowered to cool the substrate (1), fix the position of the boron element in the substrate (1), and form a stable PN junction.
7. The preparation method according to claim 5, characterized in that: Repeating step (6) can obtain a second Al2O3 passivation layer (9) with different thicknesses.
8. The preparation method according to claim 5, characterized in that: In step (7), when spin coating the SiO2 sol-gel solution, the volume of the SiO2 sol-gel solution is 20-40 μL, the rotation speed is 3500-4500 rpm / min, the spin coating time is 30-40s, the heating annealing temperature is 100-110°C, and the heating annealing time is 2-4 min.
9. The preparation method according to claim 6, characterized in that: In step (8), the temperature of the vacuum evaporation coating is 1180-2470°C and the vacuum degree is 7x10 -4 Pa, the rate for evaporating the LiF layer (7) was 0.1 KÅ / s, and the rate for evaporating the Al electrode (8) was 5.0 KÅ / s.
10. Use of the spin-coated silicon oxide passivation contact solar cell according to any one of claims 1 to 4 in the preparation of IBC solar cells or TOPCon solar cells.
